Familial clustering of lone atrial fibrillation in patients with saddleback-type ST-segment elevation in right precordial leads - Junttila, M Juhani; Raatikainen, M J Pekka; Perkiömäki, Juha S; Hong, Kui; Brugada, Ramon; Huikuri, Heikki V (European heart journal, 2007)
We recently identified a large family with a high prevalence of lone atrial fibrillation (AF) and saddleback-type ST-segment elevation in leads V(1-3), without a history of ventricular arrhythmias or syncope. On the basis of this finding, we studied whether there is a relationship between saddleback ST-elevation and lone AF. We examined 168 (mean age 50+/-8 years, 130 males) lone AF patients and 541 (mean age 50+/-6 years, 274 males) healthy subjects. The prevalence of saddleback ST-elevation was higher in the lone AF group than the control group (10 vs. 0.4%, P<0.001). None had a coved-type ST-elevation in baseline ECG or during drug challenge with ajmaline or flecainide (n=13), a family history of sudden cardiac death, ventricular tachyarrhythmias, syncope, or any other features diagnostic to the Brugada syndrome. Familial clustering of lone AF (i.e. AF in >30% of first-degree relatives) was more common among the subjects with saddleback ST-elevation (24 vs. 7%, P=0.03). Saddleback-type ST-segment elevation is a relatively common finding among patients with lone AF. The familial clustering of the disorder indicates that genetic factors may be involved in the pathogenesis of the ECG abnormality and lone AF in these patients.